The safe use of a perfusion preservation device for human kidneys - GOCHI, Mikako; KAKIZAKI, Hidehiro; TANINO, Michie; HORI, Jyunichi; TAKEI, Hidehiro; FURUKAWA, Hiroyuki; MATSUNO, Naoto; ISHII, Daisuke (Japanese Journal of Transplantation, 2020)
The expanded criteria donors (ECD) or marginal donors, including donation after cardiac death (DCD), are now accepted by most transplant centers around the world. At the same time, a greater risk of severe ischemic reperfusion injury, which may lead to delayed graft function (DGF), primary non-function, and short graft survival, has been discussed. Currently, the superiority of machine perfusion preservation is widely recognized during the preservation of kidneys, particularly those obtained from ECD and after DCD. In this study, two human kidneys that were resected because of ureteric cancer were perfused by CMP-X08, which was developed in our institution. Despite a prolonged warm ischemic time, decreased perfusion pressure and increased perfusion flow with decreasing renal resistance (RR) were seen during perfusion. However, the final RR was remarkably high. Historically, mild endothelial injury and tubular necrosis have been demonstrated. In conclusion, the safety of our newly developed machine perfusion system was confirmed. This study was approved by the Ethics Committee of Asahikawa Medical University (no.18171).